О роли собаки в религиозно-мифологических представлениях древних индоевропейских племен - Берестнев, С.И. (My University, 1999)
Berestnev S.I. On the Role of the Dog in Religious arid Mythblogical Conceptions of Indo-European Tribes In the article it is published about the unique burial of a dog in burial mound 4 of Krasnaya Gusarovka-A burial ground in Kharkov region and on the basis of enlisting archaeological and folklore — ethnographical sources it is examined the evolution of a dog's cult which is asised among hunting — collecting and cattlebreeding tribes of Europe in neolith — eneolith ages. On the basis of available data it is marked several stages in ds-velopment of the cult; these are the following: totem-deity; associated with cyclic nature rebirth — the mediator between the world of deities and the world of people.